Experimental investigation on surface quality in ultrasonic vibration assisted high speed grinding of BK7 optical glass. (2018) - Zhou, Ming; Zhao, Peiyi; Huang, Shaonan
Knowledge of surface formation mechanism plays a key role in implementing precision machining of optical glass materials. In order to evaluate the surface quality and to explore surface formation mechanism, in this paper, ultrasonic vibration assisted grinding (UVAG) experiments were carried out on BK7 optical glass by employing diamond wheel. Quite a few micro and macro brittle-fractured pits of different shapes, sizes and morphologies were observed on machined surfaces by using scanning electron microscope. Spindle rotation speed, feed rate, grinding depth and ultrasonic vibration amplitude had be found to exert significant effects on the surface generation and machined surface roughness in ultrasonic vibration assisted grinding of this kind of materials. It was also demonstrated that the value of machined surface roughness would become much smaller if the pits size was small. Based on the observation and classification of pits morphologies, the machined surfaces forming mechanism was extensively investigated in this work.